A comparison of arrangements for increasing self-consumption and maximising the value of distributed photovoltaics on apartment buildings. (15th November 2019) - Roberts, Mike B.; Bruce, Anna; MacGill, Iain
Highlights: Aggregation of loads across apartment buildings increases self-consumption of PV generation. Load aggregation through embedded network can give financial benefits to customers. Shared PV generation can add customer value to embedded network. PV distributed behind-the-meter avoids regulatory barriers of embedded network. Abstract: As subsidised feed-in-tariffs for distributed photovoltaic (PV) generation are reduced or abolished in many jurisdictions, there is growing interest in increasing self-consumption to realise greater value from rooftop PV generation. However, deployment of PV on apartment buildings lags behind other residential deployment despite the potential advantages of load aggregation. We present a study of electricity and financial flows in ten 'virtual' Australian apartment buildings under a range of technical implementations and financial arrangements, using real load profiles and simulated generation profiles. Aggregation of diverse household and shared loads, either through an embedded network or 'behind the meter' of individual dwellings, can increase self-sufficiency and self-consumption of on-site generation compared to separate systems supplying common property or individual apartments. While embedded networks can enable access to more beneficial retail arrangements, behind the meter solutions may allow residents to avoid regulatory complexities and additional costs. The relative benefits of each arrangement are dependent on building characteristics and financial settings.